Bridging a Divide: The Relationship between the Evolving Posted Workers Directive and Posted Workers Experience of Precarity - Markey, Marta Emilia (Trinity College Dublin. School of Law. Discipline of Law, 2022)
This is a sociolegal study looking at the legal framework on the posting of workers in the EU. While it may be viewed as a specialised area of EU labour law concerning barely a few million workers, it serves as a magnifying glass for the long-standing tension between the economic and the social dimensions of European integration. The overarching research question of this thesis seeks, firstly, to identify those elements of the EU framework that may have the effect of predisposing posted workers to precarious working conditions, and secondly, to propose solutions, both in the law and in the practice of its enforcement, that could potentially reduce the experience of precarity for posted workers. The architecture of the Posted Workers Directive (PWD) facilitates a degree of subtle exploitation, often referred to as social dumping , and, therefore, the posting of workers thrives whenever developmental gaps between EU Member States deepen. It is argued that the twisted design of the PWD, which framed posted workers as a service, resulted in it being ill-equipped to grant them a sufficient level of labour law protection. To address this rights deficit, the PWD has been revised twice: in 2014 and in 2018, yet some legal scholars argue that the revised EU framework remains inadequate to protect posted workers. The precarious reality of posted workers has also been confirmed by sociological studies on posted work based on empirical data. The predominant ambition of this research is to bridge the divide between doctrinal legal research and empirical sociological research on the topic. While deeply rooted in the law, it steps outside the legal context of the PWD to grasp the interaction between the evolving EU rules and their impact on the workers posting experience through qualitative interviews. This is done through a narrative inquiry based on qualitative data obtained from 29 in- depth interviews with posted workers and experts in the field. The participants stories are analysed thematically to link them to specific aspects of the EU framework and its enforcement. Interview findings shed light on the distinction in the experience of blue-collar and white-collar posted workers, and on the significance of both objective and subjective factors in determining the extent to which the posting experience entails precarity. Furthermore, the qualitative data is relied upon in order to assess the 2014-2018 reforms of the PWD framework. Based on the empirical findings, this research proposes another reform of the EU rules which may potentially further reduce the risk of precarity for posted workers.
APPROVED
Keywords: posting of workers; posted workers; EU law; Labour law; Migration; Precarity; Precarious work